The role of the mineralocorticoid receptor in immune cells in cardiovascular disease. (15th February 2022) - van der Heijden, Charlotte D. C. C.; Bode, Marlies; Riksen, Niels P.; Wenzel, Ulrich O.
Abstract : Chronic low‐grade inflammation and immune cell activation are important mechanisms in the pathophysiology of cardiovascular disease (CVD). Therefore, targeted immunosuppression is a promising novel therapy to reduce cardiovascular risk. In this review, we identify the mineralocorticoid receptor (MR) on immune cells as a potential target to modulate inflammation. The MR is present in almost all cells of the cardiovascular system, including immune cells. Activation of the MRs in innate and adaptive immune cells induces inflammation which can contribute to CVD, by inducing endothelial dysfunction and hypertension. Moreover, it accelerates atherosclerotic plaque formation and destabilization and impairs tissue regeneration after ischaemic events. Identifying the molecular targets for these non‐renal actions of the MR provides promising novel cardiovascular drug targets for mineralocorticoid receptor antagonists (MRAs), which are currently mainly applied in hypertension and heart failure. LINKED ARTICLES: This article is part of a themed issue on Emerging Fields for Therapeutic Targeting of the Aldosterone‐Mineralocorticoid Receptor Signaling Pathway. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v179.13/issuetoc